2022
DOI: 10.17977/um062v4i62022p484-494
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Kodular Materi Bola Basket Untuk Guru PJOK SMP

Abstract: Junior High School students require innovative learning, especially physical education basketball materials. The purpose of this research and development is to produce learning media of basketball materials based on kodular website and help teachers to explain basketball materials, and help students to better understand and practice basketball materials. The method used is the Research and Development method by using eight methods adjusted to the research needs. The Data collection method is carried out in way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This indicated that the Kodular-based tool led to substantial learning outcomes in Arabic language proficiency. These findings align with the effectiveness of similar Kodular-based tools, as demonstrated by (Ferdiansyah et al, 2022;Galiatsatos et al, 2016;Koderi et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This indicated that the Kodular-based tool led to substantial learning outcomes in Arabic language proficiency. These findings align with the effectiveness of similar Kodular-based tools, as demonstrated by (Ferdiansyah et al, 2022;Galiatsatos et al, 2016;Koderi et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…However, communication technology facilitating Android or Kodular-based instructional media development holds the potential for innovative solutions. Such instructional media provide flexible access, allowing learners to study at their own pace and schedule, as expressed by Pawar et al, 'with this Kodular application, students can learn at their own pace and time (Ferdiansyah et al, 2022;Mutholib et al, 2020). Educators should harness these developments to design engaging and effective instructional media in line with information technology advancements.…”
Section: Introductionmentioning
confidence: 99%
“…The innovation of learning media can have an impact on the effectiveness of learning, as it plays a crucial role in enhancing the success rate of the teaching and learning process. One form of current learning innovation can be designed using the Kodular website platform (Ferdiansyah et al, 2022). One study has demonstrated that utilizing the Kodular website can generate innovative learning media in the form of emodules that effectively enhance students' thinking abilities (Nugraheny & Wahyuningsih, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Learning media innovation can have an impact on the effectiveness of learning because it plays an important role in increasing the success rate of the teaching and learning process. One form of learning innovation can now be designed with the Kodular website base [42]. In another study, the development of learning media using the Kodular website also managed to get a score of 81% in the excellent category based on the media and material experts' tests so it was said to be very feasible [43].…”
Section: Discussionmentioning
confidence: 99%